2013
DOI: 10.1212/wnl.0b013e3182a841a3
|View full text |Cite
|
Sign up to set email alerts
|

Deletions in GRID2 lead to a recessive syndrome of cerebellar ataxia and tonic upgaze in humans

Abstract: Biallelic deletions of GRID2 lead to a syndrome of cerebellar ataxia and tonic upgaze in humans. The phenotypic resemblance and similarity in protein expression pattern between humans and mice suggest a conserved role for GRID2 in the synapse organization between parallel fibers and Purkinje cells. However, the progressive and severe cerebellar atrophy seen in the affected individuals could indicate an evolutionarily unique role for GRID2 in the human cerebellum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
88
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 95 publications
(93 citation statements)
references
References 36 publications
4
88
0
1
Order By: Relevance
“…Similar to other retina-associated genes, low Grid2 mRNA expression was found at early postnatal stages, followed by an increase during development, and reaching a steady state around adulthood. In addition, GRID2 immunostaining was shown both in human and murine retina, localizing to photoreceptor inner segments, The red bars represent a homozygous deletion of exon 2, found in ho15J mice, in the patients described by Hills et al 5 as a compound heterozygous deletion, and our proband. The blue bars represent a homozygous deletion removing both exons 3 and 4, as described in ho8/13J and tpr mice and the patients reported by Utine et al 4 The human deletion of exon 1 is a heterozygous deletion, reported by Maier et al Utine, 2013 This study the outer plexiform layer, and the ganglion cell layer.…”
Section: Discussionsupporting
confidence: 60%
See 4 more Smart Citations
“…Similar to other retina-associated genes, low Grid2 mRNA expression was found at early postnatal stages, followed by an increase during development, and reaching a steady state around adulthood. In addition, GRID2 immunostaining was shown both in human and murine retina, localizing to photoreceptor inner segments, The red bars represent a homozygous deletion of exon 2, found in ho15J mice, in the patients described by Hills et al 5 as a compound heterozygous deletion, and our proband. The blue bars represent a homozygous deletion removing both exons 3 and 4, as described in ho8/13J and tpr mice and the patients reported by Utine et al 4 The human deletion of exon 1 is a heterozygous deletion, reported by Maier et al Utine, 2013 This study the outer plexiform layer, and the ganglion cell layer.…”
Section: Discussionsupporting
confidence: 60%
“…A summary of the bioinformatics findings is given in Table 1; visualization of microhomology can be found in Supplementary Figure S1 online. Based on the results of this extensive analysis, the studied GRID2 deletions with microhomology may be caused by nonhomologous end-joining (<5-bp microhomology) or a replicative-based repair mechanism, favoring the latter because an information scar, typical of nonhomologous end-joining, was not present at the junction for our deletion and was not reported for the deletions described by Hills et al 5 The deletion without microhomology is more likely to be caused by nonhomologous end-joining. The presence of sequence motifs can result in genomic instability and the formation of a deletion.…”
Section: Identification and Characterization Of Homozygous Grid2 Delementioning
confidence: 83%
See 3 more Smart Citations